Building a Fortress of Independent Journalism: Historical Study of the Role of Aliansi Jurnalis Independen (AJI) in Indonesia, 1994-1999 - Raisye Soleh Haghia; Susanto Zuhdi; Linda Sunarti (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2025)
Abstract: The democratic transition period in Indonesia (1994-1999) became crucial for developing independent journalism. Aliansi Jurnalis Independen (AJI) emerged as a firm and strong organization that fought for press freedom and built a fortress of independent journalism amid the New Order repression. This study aims to analyze AJI's strategy in building and fighting for independent journalism in Indonesia during this period. Using historical analysis and a qualitative approach, this study explores AJI's contribution to voicing the interests of journalists, fighting for freedom of expression, and rejecting state intervention in the press. The data was collected through literature studies, analysis of organizational documents, and in-depth interviews with AJI activists. This research opens a new understanding of AJI's efforts to achieve press freedom in the New Order era through a review of AJI's strategy for developing independent journalism in Indonesia. This study's results show that AJI uses conventional strategies such as advocacy and education and innovative strategies such as networking, solidarity, and publications. These strategies have proven effective in strengthening independent journalism in Indonesia, with the realization of a freer and professional journalistic environment. Abstrak: Periode transisi demokrasi di Indonesia (1994–1999) menjadi masa krusial bagi tumbuhnya jurnalisme independen. Aliansi Jurnalis Independen (AJI) muncul sebagai organisasi yang tegas dan kuat dalam memperjuangkan kebebasan pers serta membangun benteng jurnalisme independen di tengah represi Orde Baru. Penelitian ini bertujuan untuk menganalisis strategi AJI dalam membangun dan memperjuangkan jurnalisme independen di Indonesia selama periode tersebut. Dengan menggunakan pendekatan historis dan kualitatif, studi ini menggali kontribusi AJI dalam menyuarakan kepentingan jurnalis, memperjuangkan kebebasan berekspresi, serta menolak intervensi negara terhadap pers. Data diperoleh melalui studi literatur, analisis dokumen organisasi, dan wawancara mendalam dengan aktivis AJI. Penelitian ini membuka pemahaman baru mengenai upaya AJI dalam meraih kebebasan pers di era Orde Baru, melalui peninjauan terhadap strategi-strategi AJI dalam mengembangkan jurnalisme independen di Indonesia. Hasil penelitian menunjukkan bahwa AJI tidak hanya menggunakan strategi konvensional seperti advokasi dan edukasi, tetapi juga strategi inovatif seperti membangun jaringan, solidaritas, dan penerbitan. Strategi-strategi ini terbukti efektif dalam memperkuat jurnalisme independen di Indonesia, ditandai dengan terciptanya iklim jurnalistik yang lebih bebas dan profesional.